Social Metabolism and Bioethics: A Dialogue of Knowledge (Revista Iberoamericana de Bioética, 2020)
The objective of this review article is to analyze the interdisciplinary dialogue between social metabolism and bioethics as disciplines that tend for life. The methodology is qualitative and its method is documentary review. The main conclusion is that social metabolism is an interdisciplinary approach or theory that dialogue with other disciplines needs to be able to solve the problems of exchange between human conglomerates with nature. Indeed, the guidelines such as the contributions of Bioethics can contribute to generate a language as solutions that are more in line with the needs of the present, given the conceptual richness of Bioethics and its ability to potentiate life.
Keywords: social metabolism; interdisciplinarity; life